Droplet impact dynamics on stretched textiles - Nonu Varghese; Corinne A. Stone; Miguel A. Quetzeri-Santiago; J. Rafael Castrejón-Pita (Scientific Reports)
Abstract Preventing droplets from penetrating fabrics is critical in surgical wards and the battlefield, where biological and chemical hazards are dispersed and transmitted in droplet form. Here, we study the interaction between droplets and a nylon textile using high-speed imaging. We explore various droplet impact velocities and liquids to understand the influence of liquid characteristics on the impact behaviour. Importantly, we investigate the impact dynamics of droplets on textiles subjected to various tensile forces. Critical phenomena, such as droplet penetration and capture, are analyzed. We find that the critical impact velocity for droplet penetration increases as the stretching tension in the textile decreases. Furthermore, we present a simple model to predict the critical conditions for droplet penetration and capture that takes into account the surface tension, the droplet size, density and speed, the tensile load and the textile contact angle. We validate the model through experiments, demonstrating a strong agreement. These insights hold significant implications for the design of protective garments, such as face-masks and water-repellent clothing.